A Study on the Impact of Parental Encouragement on Examination Stress and Academic Achievement among High School Sstudents - R, Sujeetha; Selvakumar, Y Stanly (Journal of Advanced Research in English & Education; Vol 7 No 2 (2022): Journal of Advanced Research in English and Education, 2022)
The study explored the relationship between parental involvement in education and academic performance of senior high school students. A person’s education is closely linked with his or her life chances, income and general well-being. Therefore, the success of students in any academic task has become a major concern to educators, parents, researchers and society. Literature indicates that there is a lack of specific or universal definition of academic performance. This is because academic performance is a multidimensional construct composed of the skills, attitudes, and behaviors of a learner that contribute to academic success in the classroom.Education has a vital role in the sustainable economic prosperity of any nation. However, this prosperity is dependent upon the academic success of the students, where academic success means the ability of the students to apply the skills and knowledge learnt at school. Academicians and education researchers have long been researching the ways and factors affecting academic achievement. Since the majority of school students spend most of their time at home with their parents and family, therefore parents and family may have a significant role in the academic achievement of school students. A volume of research has been focusing on the role of parental involvement in the academic achievement of students. Parental involvement can play an important role in enhancing their academic achievement. How to cite this article: Sujeetha R, Selvakumar YS. A Study on the Impact of Parental Encouragement on Examination Stress and Academic Achievement among High School Students. J Adv Res Eng & Edu 2022; 7(2): 11-13. DOI: https://doi.org/10.24321/2456.4370.202210